Fire-resistant and flame-retardant surface finishing of polymers and textiles: a state-of-the-art review - Ong, Yi Wen; Mohd Tohir, Mohd Zahirasri; Choong, Thomas Shean Yaw; Abdul Razak, Musab; Zainuddin, Halimatun Sakdiah; Abdul Hamid, Mohamad Rezi (Elsevier, 2022)
Polymers and textiles can be found in every facet of human everyday life particularly as household items and apparels though most of them are inherently flammable. Surface finishing is a convenient approach to endow polymers and textiles with flame retardancy without sacrificing intrinsic properties of the bulk materials. In this contribution, we present a state-of-the-art review of a variety of surface finishing approaches to provide polymers and textiles with fire-resistance. The reviewed works are organized as follows: layer-by-layer assembly, dip coating, in-situ solution-based synthesis, and brushing/spray coating. The discussion then continues with a thorough assessment of the materials' flame-retardant performances. We also attempt to shed lights on key aspects of high-performance coatings including applications of bio-based or advanced materials, synergistic combinations, microstructure and interface evaluations, multifunctional coating, and many more. We hope that this contribution provides meaningful insights for researchers to better formulate and develop new synthesis protocol to fabricate high-performance flame-retardant coating.